Kebebasan pers dan kesenjangan gender di Filipina pada masa kepemimpinan Presiden Rodrigo Duterte - Mevy Eka Nurhalizah; Muhammad Hamdan Yuwafik (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
This paper tries to describe how press freedom and gender equality in the Philippines during President Rodrigo Duterte's leadership, and to answer whether the concept of the relationship of press freedom and gender equality in the Philippines also applies. This study is a literature study through the work of other researchers obtained through journals, books and the internet. The results of the study show that the concept of the relationship between freedom of the press and gender equality also applies in the Philippines. This was evidenced by a survey from the Reporters Without Boarders agency which showed press freedom in the Philippines ranked 134 out of 180 countries in 2019, down 1 place from 2018, and a survey from the World Economy Forum which showed the Philippines ranked 16th in 2019, which means it dropped to 6th rank from 2018. Freedom of the press in the Philippines is still problematic because it is hampered by the face, culture of impunity and policies of President Rodrigo Duterte. The issue of press freedom has increased gender inequality in the Philippines. Women in the media in the Philippines contribute to the field of work and content to the media.